Analysis of Coal Seam Identification Based on Drilling Data in Nunukan Regency, North Kalimantan - Mukarramah, A. Aenul Tul; Anshariah2, Anshariah; Budiman, Agus Ardianto (CV Insight Publisher, 2024)
Coal deposition results in the formation of continuous layers with specific thicknesses and slopes. This study aimed to determine coal seams based on drilling data. The method involved correlating the rocks flanking the coal seams using AutoCAD 2014 software. The findings revealed that points BC-054, BC-045, and BC-038 belong to the same coal seam based on the associated flanking rocks. Similarly, points BC-029, BC-022, BC-004, and BC-087 were also found to be interconnected within a coal seam, sharing similar thicknesses and clamping rock layers. However, the third layer at BC-087 does not correspond with other boreholes and is categorized as a separate seam. Correlation analysis identified three coal seams with an average thickness ranging from 0.6 m to 1.7 m.